Bali as a tourist destination - students' perceptions - Shanka, Tekle; Alamsyah, Rhesa (The International Management Development Association (IMDA), 2012)
This paper presents the findings of a student survey of perceptions of a tourist destination. A convenience sample of 300 higher education students in a large Australian university participated in self-completion survey. Of these 229 students had not visited the destination in the past – hence their responses were based on an organic image of the destination. Data were factor analyzed and five components (factors) were identified. These were: scenic, relaxing, safe, accessible, and historical. Results were discussed and future research directions were suggested.